2020
DOI: 10.1182/blood-2020-133908
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib, Dexamethasone, and Daratumumab Versus Carfilzomib and Dexamethasone in Relapsed or Refractory Multiple Myeloma: Subgroup Analysis of the Phase 3 Candor Study in Patients with Early or Late Relapse

Abstract: Introduction: Although outcomes for patients with multiple myeloma (MM) have improved with recent advances in treatment, relapse is still frequent. Early relapse is associated with poorer outcomes (Majithia et al., Leukemia 2016;30:2208-13) and is thought to reflect more aggressive disease, particularly within 12 months of autologous stem cell transplantation (ASCT). In the randomized phase 3 CANDOR study, progression-free survival (PFS) was significantly improved in patients with relapsed or refractory MM (RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Some sub group analy sis in phase 3 tri als focused on early relapses, defined as those occur ring within the first 12 to 18 months after the pre-vi ous ther apy, show ing that the addi tion of carfilzomib to Rd or daratumumab to Rd vs Rd in the ASPIRE and POLLUX trials resulted in a sig nifi cant ben e fit for the tri ple com bi na tion com pared with Rd. A sim i lar effect has been recently reported with the addi tion of daratumumab to bortezomib or carfilzomib [28][29][30][31] (Table 2). *High-risk defi ni tion: gene expres sion pro fil ing high risk, t(14;16), t(14;20), del(17p), amp1q21, plasma cell leu ke mia, ele vated serum LDH (…”
Section: Management Of Func Tional High-risk Patientssupporting
confidence: 56%
“…Some sub group analy sis in phase 3 tri als focused on early relapses, defined as those occur ring within the first 12 to 18 months after the pre-vi ous ther apy, show ing that the addi tion of carfilzomib to Rd or daratumumab to Rd vs Rd in the ASPIRE and POLLUX trials resulted in a sig nifi cant ben e fit for the tri ple com bi na tion com pared with Rd. A sim i lar effect has been recently reported with the addi tion of daratumumab to bortezomib or carfilzomib [28][29][30][31] (Table 2). *High-risk defi ni tion: gene expres sion pro fil ing high risk, t(14;16), t(14;20), del(17p), amp1q21, plasma cell leu ke mia, ele vated serum LDH (…”
Section: Management Of Func Tional High-risk Patientssupporting
confidence: 56%
“…The definitions used to classify early and late relapse patients in the current study were the same as those used in the phase III CANDOR, CASTOR, and POLLUX subgroup analyses that evaluated triplet regimens based on another anti-CD38 monoclonal antibody, daratumumab. 20 , 27 Post hoc subgroup analyses of the CANDOR (daratumumab plus Kd vs. Kd), CASTOR (daratumumab plus bortezomib and dexamethasone [D-Vd] vs. Vd), and POLLUX (daratumumab plus lenalidomide and dexamethasone [D-Rd] vs. Rd) studies reported PFS HR=0.4-0.7, and ≥CR rates of 16.0-53.0% versus 0-17.0% in early relapse patients who had received daratumumab-based regimens versus control regimens, respectively. 20 , 27 MRD- (10- 5 ) rates for early relapse patients were 13-30% with D-Vd /D-Rd versus 0-4% with Vd/Rd in CASTOR/POLLUX and were not reported for CANDOR.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were classified into early or late relapse subgroups based on previously established definitions. 20 , 21 Early relapse was defined as relapse that occurred <12 months from initiation of the most recent line of therapy for patients with ≥2 prior lines of therapy, <18 months for patients with one prior line of therapy, or <12 months following frontline ASCT. Late relapse subgroup included patients who relapsed ≥12 months from initiation of the most recent line of therapy for those with ≥2 prior lines of therapy and ≥18 months for patients with one prior line of therapy.…”
Section: Methodsmentioning
confidence: 99%